Cardiomyocytes, endothelial cells and cardiac fibroblasts: S100A1's triple action in cardiovascular pathophysiology. (May 2015) - Rohde, David; Busch, Martin; Volkert, Anne; Ritterhoff, Julia; Katus, Hugo A; Peppel, Karsten; Most, Patrick
ABSTRACT : Over the past decade, basic and translational research delivered comprehensive evidence for the relevance of the Ca 2+ -binding protein S100A1 in cardiovascular diseases. Aberrant expression levels of S100A1 surfaced as molecular key defects, driving the pathogenesis of chronic heart failure, arterial and pulmonary hypertension, peripheral artery disease and disturbed myocardial infarction healing. Loss of intracellular S100A1 renders entire Ca 2+ -controlled networks dysfunctional, thereby leading to cardiomyocyte failure and endothelial dysfunction. Lack of S100A1 release in ischemic myocardium compromises cardiac fibroblast function, entailing impaired damage healing. This review focuses on molecular pathways and signaling cascades regulated by S100A1 in cardiomyocytes, endothelial cells and cardiac fibroblasts in order to provide an overview of our current mechanistic understanding of S100A1's action in cardiovascular pathophysiology.